The Critical Hazard Factors for Animal Health Workers: a Call for Action - Dewi, Kharisma; Santi, Garini Purwara; Jaladara, Vena (BKM Public Health and Community Medicine, 2024)
Background: Humans, animals, and the environment are always intertwined in an inseparable interaction cycle, as explained through the One Health approach. One entity's health affects the others. Animal health workers are one profession at high risk of zoonotic disease transmission, which leads to public health problems. Unfortunately, occupational safety and health practices in this industry still fall short of expectations. Purpose: To increase awareness about the importance of workplace safety for animal health workers, including veterinarians, paramedics, and field officers. To recommend strategies for preventing zoonotic infection transmission among veterinary workers by implementing hygiene procedure then followed by regular health screenings, mandatory vaccinations, and enhanced training programs. Discussion: Occupational safety and health (OSH) in veterinary practice is crucial, yet there lacks specific clarity in protecting workers directly involved with animals, including veterinarians, despite existing foundational guidelines for policy development. The National Indonesian Work Competency Standards (SKKNI) outlined in the Minister of Manpower Regulation No. 394 of 2014 regarding the Determination of National Indonesian Work Competency Standards in the Professional, Scientific, and Technical Services Categories, Main Group of Animal Health Services, in the Field of Animal Health Management, provide a framework, but gaps remain. Current OSH practices for these professionals are inadequate especially the immediate risk posed by zoonotic diseases from direct contamination, as well as a range of other workplace dangers including handling animals with potential bites and scratches, ergonomic issues, slips, trips, falls, hazards related to motor vehicles, noise exposure, ionizing radiation, and radiation safety concerns, risks linked to needlestick injuries, and physiological stress factors. This shortfall is exacerbated by the lack of courses on zoonotic infection safety in animal health practitioners for veterinary students' curricula which include protective measures for their profession, such as advance hygiene procedure, screening, and vaccination protocols. To address these challenges, we advocate for the implementation of comprehensive measures such as the implementation of hygiene procedure then followed by regular health screenings, mandatory vaccinations in the future, and enhanced training programs. These initiatives will not only safeguard the health of animal health workers but also align with broader public health objectives by curbing the transmission of zoonotic infections. Conclusion: In conclusion, urgent action is needed to address the lack of awareness among veterinarians regarding occupational safety and health practices. The risks of zoonotic disease transmission to animal health workers are significant, requiring immediate implementation of preventive measures such as regular health screenings, mandatory vaccinations, and enhanced training programs. Delaying action could have serious consequences, emphasizing the need to prioritize the safety of these professionals without delay. Additionally, it is important to develop clear policies and procedures regarding workplace safety in the animal health sector, as well as to promote a culture of safety in the workplace. Open communication between the government, relevant institutions, and the animal health worker community is also key to finding effective solutions to enhance their safety.